Strategi dan Manajemen Dakwah Majelis Tafsir Al Qur’an melalui MTA TV Surakarta - Silvia Riskha Fabriar; Kurnia Muhajarah (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2021)
Da'wah can be done with various strategies according to the state of mad'u. Management in the organization is structured in such a way that da'wah activities run well and according to purpose. The Qur'an Tafsir Council (MTA) is one of the da'wah institutions that carry out its da'wah with various methods, one of which is through television media among other da'wah media. MTA TV presents various da'wah programs in accordance with the vision of the MTA institution. The purpose of this study is to see how the MTA propaganda strategy through television is also side by side with other media. The author uses a qualitative descriptive research method. The findings of this study indicate that MTA through MTA TV can carry out their da'wah effectively because they are able to reach a wider audience. MTA TV is also able to adapt to the times so that this channel can survive, in addition to utilizing social networks that are in great demand by the public. However, on the other hand, the audience of listeners is still limited among Muslims who are members of this da'wah institution and the variety of programs is not so diverse.